The PELGAS survey: Ship-based integrated monitoring of the Bay of Biscay pelagic ecosystem. (September 2018) - Doray, Mathieu; Petitgas, Pierre; Romagnan, Jean Baptiste; Huret, Martin; Duhamel, Erwan; Dupuy, Christine; Spitz, Jérome; Authier, Matthieu; Sanchez, Florence; Berger, Laurent; Dorémus, Ghislain; Bourriau, Paul; et al.
Highlights: The PELGAS integrated survey conducted since 2000 in spring in the Bay of Biscay is presented. PELGAS objectives have switched from the study of the anchovy stock status to ecosystem monitoring. Spatially-explicit data of the main pelagic ecosystem components have been collected since 2000. Multidisciplinary collaborative working and enough vessel space were critical success factors. Finding relevant common scales is essential to analyse ecosystem data within or across compartments. Abstract: The Pélagiques Gascogne (PELGAS) integrated survey has been developed by a multidisciplinary team of Ifremer and La Rochelle University scientists since 2000, joined by commercial fishermen in 2007. Its initial focus was to assess the biomass and predict the recruitment success of anchovy in the Bay of Biscay in spring. Taking advantage of the space and versatility of R/V Thalassa II, sampling has been progressively extended to other ecosystem components. PELGAS therefore further developed the second objective of monitoring and studying the dynamic and diverse Biscay pelagic ecosystem in springtime. The PELGAS survey model has allowed for the establishment of a long-term time-series of spatially-explicit data of the Bay of Biscay pelagic ecosystem since the year 2000. Main sampled components of the targeted ecosystem are: hydrology, phytoplankton, mesozooplankton, fish and megafauna. The survey now provides two main ecosystem products: standard raster maps of ecosystem parameters, and a time series dataset of indicators of the Bay of Biscay pelagic ecosystem state. They are used to inform fish stock and ecosystem-based management, and support ecosystem research. The present paper introduces the PELGAS survey, as a practical example of an integrated, vessel-based, ecosystem survey. The evolution of the PELGAS scientific team and sampling protocols are presented and analysed, to outline factors crucial to the success of the survey. Data and results derived from PELGAS are reviewed, to exemplify scientific questions that can be tackled by integrated ecosystem survey data. Advantages and challenges of the survey are discussed and put into the context of marine ecosystem surveys in the European Marine Strategy Framework Directive and the Common Fisheries Policy.